PENGARUH GAME-BASED LEARNING BERBANTUAN GAME EDUKATIF “AYO MENDAUR ULANG” TERHADAP KREATIVITAS SISWA SEKOLAH DASAR - Dista Olivia Efranji; Sholikhan, Sholikhan; Arnelia Dwi Yasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Elementary school learning is generally still oriented toward mastery of subject matter, so students’ creativity has not been fully facilitated. Therefore, a learning strategy is needed that can create an active and enjoyable learning process while Giving pupils the chance to freely share their thoughts. The purpose of this study is to investigate how primary school students' creativity is affected when the game-based learning approach is used in conjunction with the educational game "Ayo Mendaur Ulang." This study used a quasi-experimental design and a quantitative methodology. Fifth-graders who were split between an experimental class and a control class made up the sample. Essay exams in the form of pretest and posttest were used to collect data on students' inventiveness. The gathered data were then examined using a t-test for hypothesis testing, homogeneity testing, and normality testing. The findings revealed a substantial difference in the inventiveness of students who were taught using the game-based learning model with the use of instructional games compared to those who were taught without the use of games. According to these results, using game-based learning with the help of the educational game "Ayo Mendaur Ulang" enhances students' creativity and is suggested as a substitute teaching method in primary school.